The m6A-methylated mRNA pattern and the activation of the Wnt signaling pathway under the hyper-m6A-modifying condition in the keloid - Lin, Can-Xiang; Chen, Zhi-Jing; Peng, Qi-Lin; Xiang, Ke-Rong; Xiao, Du-Qing; Chen, Ruo-Xi; Cui, Taixing; Huang, Yue-Sheng; Liu, Hong-Wei (Frontiers in Cell and Developmental Biology, 2022)
Abstract Purpose: The present study was carried out to investigate the global m6A modified RNA pattern and possible mechanisms underlying the pathogenesis of keloid. Method: 14 normal skin and 14 keloid tissue were firstly collected on clinic. Then 3 samples from each group were randomly selected to be verified with the Western Blot to determine the level of methyltransferase and demethylase. The total RNA of all samples in each group was isolated and subjected to the analysis of MeRIP-sequencing and RNA-sequencing. With the software of MeTDiff and htseq-count, the m6A peaks and differentially expressed genes (DEGs) were determined within the fold change > 2 and p-value < 0.05. The top 10 pathways of m6A modified genes in each group and the differentially-expressed genes were enriched by the Kyoto Encyclopedia of Genes and Genomes signaling pathways. Finally, the closely associated pathway was determined with the Western Blot and immunofluorescence staining. Results: There was a higher protein level of WTAP and Mettl3 in the keloid than in the normal tissue. 21,020 unique m6A peaks with 6573 unique m6A-associated genetic transcripts appeared in the keloid samples. In the normal tissue, 4028 unique m6A peaks with 779-associated modified genes appeared in the keloid. In the RNA-sequencing, there were 847 genes significantly changed between these groups, transcriptionally. The genes with m6A methylated modification and the upregulated differentially expressed genes between two tissues were both mainly related to the Wnt signaling pathway. Moreover, the hyper-m6A modified Wnt / β-catenin pathway in keloid was verified with western blotting. From immunofluorescence staining results, we found that the accumulated fibroblasts were under a hyper-m6A condition in the keloid and the Wnt/β-catenin signaling pathway was mainly activated in the fibroblasts. Conclusion: The fibroblasts in the keloid were under a cellular hyper-m6A methylated condition, and the hyper-m6A modified highly-expressed Wnt / β-catenin pathway in the dermal fibroblasts might promote the pathogenesis of keloid.